ESTABLISHMENT OF TYPICAL DOSE VALUE FOR INTERVENTIONAL RADIOLOGY EXAMINATION IN RADIOLOGY DEPARTMENT, HOSPITAL PENGAJAR UPM - Zurihanaz, Atika Amylia; Mohd Noor, Noramaliza (Asian Journal Of Medical Technology, 2023)
Angiography is commonly used as a diagnostic imaging tool for diagnosing and treating the patient from simple to complex examination. Despite the advancement in imaging technologies, the radiation dose to the patient remains a concern when using this procedure. Diagnostic Reference Levels (DRLs) are used to identify the amount of dose exposed to the patient and monitor the high dose received by an individual in a specified radiological procedure. The aim of this study is to establish Institutional Diagnostic Reference Levels (DRLs) based on median data dose distribution for cerebral examination (cerebral angiography and stroke thrombectomy) and compared with established Malaysian National Diagnostic Reference Levels (NDRLs). The Dose Area Product (DAP) and fluoroscopy time were recorded using clinical data from the participating modality from 1 January 2022 until 31 December 2022 at Teaching Hospital Universiti Putra Malaysia (HPUPM). The data collected for each procedure with a minimum recommended number of patients (at least 30) required to propose a DRL for each examination type within the data collection period. The mean value, standard deviation, median value, and 3rd quartile were calculated using Microsoft Excel Version 2013. The Typical Dose Value for the interventional procedure was defined as the median of the distribution of DRL quantities and required further optimization. The distribution of DAP values for the cerebral angiogram and stroke thrombectomy ranged between 5.05 mGy.m2 to 31.80 mGy.m2 and 7.03 mGy.m² to 43.23 mGy.m² respectively. The institutional DRLs for cerebral angiogram (10.60 mGy.m2) and stroke thrombectomy (21.80 mGy.m2) were higher than the established Malaysian National DRL. From the findings, stroke thrombectomy examinations recorded the highest Typical Dose value follow by cerebral angiogram examination. Generally, the factors that can affect DRL values are a patient-related factor, equipment-related factor, the complexity of the procedures, operator’s experience in handling the machine and interventional radiologist experience that can contribute to various results.